PENGARUH ARANG DAN CUKA KAYU TERHADAP PENINGKATAN PERTUMBUHAN DAN SIMPANAN KARBON - Sri Komarayati; Gusmailina; Gustan Pari (Jurnal Penelitian Hasil Hutan, 2014)
The research aimed to look into the growth responses of sengon, jabon, and agarwood seedlings; and to examine the carbon (C), nitrogen (N), phosphor (P), and potash (K) contents in soil as well as in the biomass portions of those three plant species (i.e. their leaves, stems, and roots) after being added with charcoal and wood vinegar. It also intended to explore the potency of carbon store in such plant-biomass portions. The charcoal addition was conducted by mixing it with soil evenly and homogenously, while wood-vinegar incorporation proceeded by spraying it onto the soil. For taking care of the plants, the wood vinegar was sprayed periodically to their stems, twigs, and leaves. Results revealed that the growth of sengon seedlings achieved the greatest in height (156.33 cm) and in diameter (20.08 mm), attributed to the addition of wood vinegar (2%) and charcoal (10%). For jabon seedlings, the greatest growth in height (89.17 cm) and in diameter (19.22 mm) occurred due to addition of wood vinegar (4%) and charcoal (20%). For agarwood seedlings, the greatest growth height (72.20 cm) and in diameter (18.29 mm). Besides, the addition of charcoal and wood vinegar could not also bring about the increase in consecutively nutrient contents (e.g. C, N, P. and K), biomass weight, and carbon store, which varied in the leaves, stems, and roots, in accordance to the percentages/ dosages of those two agents as added.